Personal Values as Predictor of Ethical Behavior of Managers: A Study of Select Indian Public Sector Undertakings - Pattanaik, A. K.; Modi, Sanjay; Budhiraja, Sunil (Prabandhan: Indian Journal of Management, 2015)
In this study, an attempt was made to capture the personal values possessed by Indian managers and measuring their influence on the ethical behavior of the same. A construct was hypothesized after reviewing existing literature on the identified variables. Data were collected from 150 senior managers of two public sector petroleum and natural gas companies of India. As a leading outcome, a set of 12 personal values and four ethical, unethical behavior factors were extracted by applying exploratory factor analysis. In the second phase of the study, it was observed that out of the 12 personal values, five had a direct and significant influence on the ethical behavior of the respondent managers. The paper offered an in-depth analysis by making use of multivariate analysis. The findings of the study confirmed that Self Orientation and Materialistic Orientation were the major personal values which promoted unethical behavior among managers. On the contrary, Selfless Work, Conformity to Authority, and Achievement Orientation discouraged unethical behavior among managers. The findings of the study validated the results of some of the existing studies conducted in the international context and attempted to answer various questions posed or unexplored in literature. The research is original and will add value to researchers and organizations to understand the importance of various personal values and their influence on ethical behavior of managers.